New Insight into Mixing Fluoride and Chloride in Bioactive Silicate Glasses - Xiaojing Chen (Nature Portfolio, 2018)
Abstract Adding fluoride into bioactive glasses leads to fluorapatite formation and a decrease in glass transition temperature. Recently, chloride has been introduced into glasses as an alternative to fluoride. The presence of the large chloride ion lowers glass crystallisation tendency and increases glass molar volume, which effectively facilitates glass degradation and bone-bonding apatite-like layer formation. However, there is no information regarding the effect of mixing fluoride and chloride on the glass structure and properties. This study aims to synthesize mixed fluoride and chloride containing bioactive glasses; investigate the structural role of fluoride and chloride and their effects on glass properties. The chloride content measurements reveal that 77–90% of chloride was retained in these Q2 type glasses. Glass transition temperature reduced markedly with an increase in CaX2 (X = F + Cl) content, while the glass molar volume increased. 29Si MAS-NMR results show that the incorporation of mixed fluoride and chloride did not cause significant change in the polymerization of the silicate network and no detectable concentration of Si-F/Cl bands were present. This agrees with 19F NMR spectra showing that F existed as F-Ca(n) species.